Analysis of Parents' Needs to Educate Down Syndrome Adolescents About Menstrual Personal Hygiene - Sarah Nur Rachmawati (Journal of Disability, 2021)
The background of this research is the lack of understanding of parents and the absence of a manual regarding menstrual personal hygiene for adolescent girls with Down syndrome. The purpose of this study was to determine the need for the right media to increase parents' understanding of menstrual personal hygiene for children with Down syndrome. The subject selection technique was purposive sampling which was adjusted to the criteria that had been made by the researcher, namely 35 parents with the characteristics of having Down syndrome young women who menstruating, early adulthood to middle adulthood, and domiciled in Karisidenan Surakarta. Data collection techniques using questionnaires and interviews. Data analysis used descriptive analysis based on the results of SPSS and interviews. The results of the study obtained a final value of 3.35 which can be defined as very needy. In the interview, it was found that parents needed a guidebook on menstrual personal hygiene for adolescent girls with Down syndrome. It can be concluded that parents really need a guidebook regarding menstrual personal hygiene for adolescent girls with Down syndrome.